The Role of Guru Penggerak Support in the Success of the Primary School Teacher Professional Education Program - Madona, Ade Sri; Wirnita, Wirnita; Yuza, Arlina; Azkiya, Hidayati; Saleh, Amri; Ramadhani, Ulfah; Anggraini, Olivia (Jurnal Inovasi Pendidikan Dasar, 2025)
In achieving national education goals, the quality of teachers’ instruction is a key factor in nurturing students’ potential. Teachers play a crucial role in developing teaching quality in schools and determining student success, especially in the teaching and learning process. Professional teachers are the most influential factor in creating better educational outcomes. One way to improve pedagogical skills is through the Teacher Professional Education Program (PPG). To realize this, support from driving teachers is essential because they create an environment that enables teachers to share knowledge, experiences, and resources to enhance learning quality. This study focuses on the success of PPG from the perspective of driving teachers. Using a descriptive qualitative method, data were analyzed from various informants. The findings show that driving teachers demonstrate teaching innovations, motivate others to improve pedagogy, and provide significant support for teacher professional development. Participation in the program positively impacts pedagogical abilities of prospective teachers.